Broadcast media policy in Nigeria: across many dispensations (2010)
"The present article traces the adaptation of media and communication institutions to the political, economic, ethnic and cultural realities of Nigeria from the colonial (very British) dispensation, to the military and finally to the civilian in the last ten years. The form of the adaptation very largely reflects the political interests of the group in power, but there has always been a negotiation with more prominent interest groups. Ironically, the military, though it defended its interests, tended to be less politically partisan than the civilian governments. The major weakness in Nigerian communication policy making is the absence of strong continuous public involvement and consistent private sector and civil society participation. Typically, a small group of unrepresentative experts prepares the documents and there is little transparent consultation with the public. This produces some adaptation, but with a media system that protects the reigning political power. "